STAYING OR LEAVING? HOW ORGANIZATIONAL COMMITMENT MEDIATES THE LINK BETWEEN JOB INSECURITY AND TURNOVER INTENTION IN PT. SAMPHARINDO PERDANA - Rahmadani, Luthfia; Putra, Febrianur Ibnu Fitroh Sukono; Kristina, Erin; Hapsari, Dian Indriana (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2025)
This research aims to determine the effect of job insecurity on turnover intention with organizational commitment as a mediator at PT. Samharindo Perdana. The population used in this research was 97 employees of PT. Sampharindo Perdana used the census method sampling technique, 97 respondents were used in this research. The data used is primary data, with data collection methods from questionnaires. The analytical tool in this research uses path analysis to test the research hypothesis, and the calculations use the IBM SPSS 29 statistical program. The results of this research show that job insecurity has a negative effect on organizational commitment, job insecurity has a positive effect on turnover intention, organizational commitment has a negative effect on turnover intention, and Organizational commitment mediates the effect of job insecurity on turnover intention.